Un marco metodologico para la investigacion en campos de agricultores (version resumida) - Woolley, Jonathan N.; Pachico, Douglas H. (International Center for Tropical Agriculture, 1987)
A detailed description of the methodological framework for on- farm research is included; it provides a logical sequence for the activities carried out in an agricultural subsystem and clarifies the objectives for each stage. This framework has been adapted by the CIAT Bean Program based on its experience with several national programs during 1982-86. The steps to be followed within the framework are selection of priority areas, characterization of agricultural practices, analysis of the problems, availability of resources, collection of secondary information, characteristics of the area, surveys, essay planning, special studies, technology evaluation, dissemination, and promotion. (CIAT)